International portability of health-cost cover: Mobility, insurance, and redistribution - Martin Werding; Stuart McLennan (Center for Economic Studies and ifo Institute (CESifo), 2012)
Public health insurance and other arrangements covering health-costs effectively provide insurance against changes in health status. These arrangements engage in burden-smoothing over the life cycle and entail various elements of redistribution. Lack of portability regarding this type of cover may impede international mobility and create financial losses or windfall gains on various sides, which can lead to risk segmentation across national health systems. Existing portability rules do not fully address these problems. In this paper, we try to clarify the implications of mobility for typical systems covering health costs and the requirements which have to be met to ensure full portability. When individuals are internationally mobile, compensating payments are needed based on changes in expected net costs in both of the health funds involved. Illustrative simulations show that this approach may be operative under real-world conditions.
Keywords: F22; F55; H51; H73; J60; 330; social insurance; health costs; migration; international portability; fiscal externalities; risk segmentation; Gesetzliche Krankenversicherung; Internationale Wanderung; Einkommensumverteilung; Externer Effekt; Theorie